Access of migrant gold miners to compensation for occupational lung disease: Quantifying a legacy of injustice - Rodney Ehrlich; Stephen Barker; Vivian W.L. Tsang; Barry Kistnasamy; Annalee Yassi (Elsevier, 2021)
Background: A legacy of the South African gold mining industry, now in decline, is a large burden of silicosis and tuberculosis among former migrant miners from rural South Africa and surrounding countries, particularly Lesotho and Mozambique. This neglected population faces significant barriers in filing claims for compensation for occupational lung disease. The objective of the study was to gain insight into the extent of such barriers, particularly for former miners and cross-border migrants. Methods: The database of a large gold mining company and the statutory compensation authority were analyzed for the period 1973-2018 by country of origin, age, and employment status at the time of claim filing. Proportions and odds ratios (ORs) for each of the compensable diseases were calculated by the above variables. Processing delays of claims were also calculated. Results: Annual company employment declined from 240,718 in 1989 to 43,024 in 2018 and the proportion of cross-border migrants within the workforce from 51.0 to 28.1%. The compensation database contained 68,612 claims. The majority of compensable claims in all diagnostic categories were from active miners. The odds of cross-border miners relative to South African miners filing a claim depended on employment status. For example, the OR for Lesotho miners filing while in active employment was 1.86 (95% CI 1.81, 1.91), falling to 0.94 (95% CI 0.91, 0.98) among former miners. The equivalent findings for Mozambiquan miners were 0.95 (95% CI 0.91, 1.00), falling to 0.44 (95% CI 0.41, 0.47). Median processing delays over the whole period were from 1.1 years from filing to adjudication, and 3.8 years from filing to payment. Conclusions: The findings provide a quantitative view of differential access to occupational lung disease compensation, including long processing delays, among groups of migrant miners from the South African gold mines. There is a deficit of compensable claims for silicosis and silico-tuberculosis among former miners irrespective of country of origin. While cross-border miner groups appear to file more claims while active, this is reversed once they leave employment. Current large-scale efforts to provide medical examinations and compensation justice to this migrant miner population need political and public support and scrutiny of progress.